Pediatric myelofibrosis: WHO 2024 update on myeloproliferative neoplasms calling?. Issue 5 (5th March 2020) - Mishra, Priyanka; Halder, Rohan; Aggarwal, Mukul; Seth, Tulika; Mahapatra, Manoranjan; Pati, Hara Prasad; Saxena, Renu; Tyagi, Seema
Abstract: Objectives: Pediatric myelofibrosis is a rare entity with the largest reported series of 19 cases. We describe here the clinicopathological spectrum and outcomes of 15 cases of pediatric myelofibrosis. Methods: Case files of myelofibrosis of patients less than 18 years were retrieved from January 2016 to January 2019, and patients with idiopathic myelofibrosis after exhaustive work‐up were studied. Their clinicopathological profiles were studied and then followed up for resolution and malignant transformation. Results: Of the 15 cases of idiopathic myelofibrosis, transfusion‐dependent anemia (14/15) was most common presentation. Only one patient showed leukoerythroblastosis with dacryocytes. Myeloid hyperplasia was seen in 13 of 15 patients and megakaryocytic hyperplasia in 10 patients. Dysmegakaryopoiesis was seen in 8 of 15 patients, and only three had small loose megakaryocytic clustering. None showed hyperchromatic megakaryocytes, intrasinusoidal hematopoiesis, or osteosclerosis. One patient with trisomy 8 tested positive for JAK2V617F. Bone marrow biopsy was hypercellular in 13, and 8 had world health organization (WHO) MF‐3 fibrosis. None of the patients developed malignancy, one had spontaneous resolution, and one patient required allogenic stem cell transplant. Conclusions: Pediatric myelofibrosis is a distinct entity from primary myelofibrosis in adults and merits mention in the WHO manual as a distinct entity.